Kontribusi Pengetahuan Lokal terhadap Ketahanan Lingkungan dalam Menghadapi Perubahan Iklim - Yayan Surayan; Maki Almanan; Robi Putrawanto (Trends Research of Environmental Studies, 2025)
Climate change poses increasing pressure on environmental and social systems in various regions, particularly on communities that depend directly on natural resources. In this context, local knowledge becomes an important element in building environmental resilience because it is rooted in communities’ long-term experience in interacting with their environment. This study aims to examine the contribution of local knowledge to environmental resilience in the face of climate change, emphasizing the role of such knowledge in adaptation, natural resource management, and the strengthening of social-ecological systems. This study employs a qualitative approach with a descriptive-exploratory design. Data were collected through in-depth interviews, focus group discussions, and participatory observation of communities that still actively practice local knowledge. Data analysis was conducted thematically to identify forms of local knowledge, its contribution to environmental resilience, and the social and cultural factors that influence its effectiveness. The results indicate that local knowledge contributes significantly to enhancing environmental resilience through communities’ ability to recognize local indicators of climate change, adjust natural resource management practices, and build collective responses to climate risks. Local knowledge also plays a role in maintaining ecosystem service functions, supporting community health resilience, and strengthening social cohesion. In addition, local knowledge is dynamic and adaptive, although it faces challenges in the form of knowledge erosion and limited recognition in formal policy frameworks. This study affirms the importance of integrating local knowledge into climate change adaptation efforts and sustainable environmental management.